Uso del podcast con fines de entretenimiento en estudiantes universitarios, caso de estudio, Universidad Nacional de Loja. - Hurtado Patiño, José Fernando (2024)
This research analyzes the Podcast as a modern digital communication medium and its creation formats, as well as the distribution of content and its acceptance and influence on its followers, with the aim of identifying the use and consumption, the themes, the levels of familiarity, participation, and interaction of the Podcast for entertainment purposes in students of the National University of Loja. The methodology used was a mixed qualitative and quantitative investigation, 354 surveys were applied to university students through the Google Forms platform and 2 interviews with experts on the subject. The results reflected the participation of 42% of young people between 21 and 25 years of age, meaning the majority of respondents. Due to this collaboration, youth trends in the use of Podcasts were discovered, demonstrating a greater inclination for entertainment formats without specifying the content, or in other words the content does not bother the listener or follower, rather the entertainment format captivates and attracts, above all, young students who, in accordance with their daily routine, seek an alternative escape from traditional learning environments. The use and promotion of Podcasts in educational environments is suggested, giving rise to entertaining and educational formats, considering that young students express acceptance of modern, but underutilized, digital media. Keywords: Podcast, entertainment, students, university students, entertainment format.